Unsettling Entrepreneurship Education - Karin Berglund; Ulla Hytti; Karen Verduijn (Sage, 2022)
This special issue confronts taken-for-granted views on entrepreneurship education (EE), raises critical questions both about EE and how it is taught, and allows investigations of the potential dark sides of entrepreneurship and EE. The contributions in this issue challenge our teaching positions and evoke a pedagogical approach to invention where curiosity, cocreation, though-provoking questions can follow.